Polarization analysis of birefringence in uniaxially deformed silicon crystals - Berezhinsky, L.I.; Berezhinsky, I.L.; Pipa, V.I.; Matyash, I.Ye.; Serdega, B.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The birefringence induced by uniaxial compression in low-doped silicon
crystals was investigated both theoretically and experimentally. The circular components
of the Stokes vector in the transmission and reflectance radiation are measured as a
function of external pressure by using the method based on the modulation of radiation
polarization. The value of the Brewster constant was obtained for absorption (λ =
0.63 µm) and transparence (λ = 1.15 µm) regions. The obtained experimental data are in
a good agreement with calculation results based on the anisotropy model of dielectric
properties within the framework of the Hook law. Shown is the practical importance of
the polarization analysis in researching anisotropy of dielectric properties of materials.